Unraveling the multifaceted benefits of physical exercise: a comprehensive review of body composition, metabolic regulation, and systemic health - Zhang, Shengxuan; Xu Lou, Inmaculada; Deshpande, Sammit Vishram; Sun, Lei; Hamza, Ali; Ali, Kamran; Chen, Qilan (Frontiers in Nutrition, 2026)
Obesity, a significant comorbidity for various cardiovascular and respiratory diseases, demands individualized and effective management strategies. Without appropriate intervention, obesity can severely compromise an individual’s health. Achieving weight management is feasible through the application of evidence-based knowledge and sustained commitment. Incorporating diverse forms of physical exercise—such as High-Intensity Interval Training (HIIT) and Moderate-Intensity Continuous Training (MICT)—in combination with tailored dietary habits can optimize outcomes for affected individuals. In fact, dietary regulation remains the cornerstone of any weight management program, especially among adolescents and adults facing modern lifestyle challenges. When paired with an exercise regimen aimed at reducing adipose tissue, this combined approach effectively facilitates weight control. Moreover, obesity is characterized by chronic low-grade systemic inflammation and is closely linked to numerous metabolic disorders, including the highly prevalent Diabetes Mellitus. This connection is largely attributable to obesity’s profound impact on hormonal regulation, particularly in the development of insulin resistance. For individuals who are unable to manage their weight through conventional means, bariatric surgery may be considered in advanced cases. However, post-surgical care—comprising proper dietary management and regular physical exercise—is essential for achieving and maintaining favorable outcomes. In this literature review, recent articles from the past 5 years examining the benefits of physical exercise on obesity were analyzed. The findings reveal that different modalities of physical exercise influence weight loss, adipose tissue reduction, body composition, metabolism, physical capacity, cardiorespiratory function, insulin regulation, inflammation, psychological adaptations, hormonal balance, gut microbiota, as well as factors related to pregnancy and aging. Notably, the benefits derived from physical exercise vary according to the specific type of activity performed. Consequently, when prescribing an exercise regimen, it is crucial to align the program with the individual’s specific therapeutic objectives.